Capturing carbon and conserving biodiversity : the market approach - Swingland, Ian R. (Ian Richard), 1946- (Earthscan Publications, 2003)
For decades conservation has been based on the donor-driven principle. It hasn't worked. For centuries, environmental pollution or degradation has been addressed by the same attitude: the 'Polluter Pays' principle. That hasn't worked either. The cycle has to stop. But while everyone talks about using a market-driven approach, few know how to do it. Faced with the situation on the ground what do you do? What is happening? How can you engage a system so that it is self-sustaining and the people self-motivated? This study explores how the growing market in carbon can help to conserve carbon-based.